Comparative efficacy of five approved Janus kinase inhibitors as monotherapy and combination therapy in patients with moderate-to-severe active rheumatoid arthritis: a systematic review and network meta-analysis of randomized controlled trials - Cai, Wenting; Tong, Rui; Sun, Yue; Yao, Yao; Zhang, Jinping (Frontiers in Pharmacology, 2024)
The European League of Rheumatology ( EULAR ) guidelines recommend Janus kinase(JAK)inhibitors for patients with moderate to severe rheumatoid arthritis ( RA ) who are insensitive or under-responsive to conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs). But there was no recommendation for which one was preferred in five currently approved JAK inhibitors.The objective of this network meta-analysis (NMA) study was to evaluate the efficacy of five JAK inhibitors as monotherapy and combination therapy in patients with moderate-to-severe active RA.: The randomized controlled trials (RCTs) of tofacitinib ， baricitinib ， upadacitinib ， filgotinib and peficitinib as monotherapy or combined with csDMARD in the treatment of active RA were searched in database of PubMed, Embase, Web of Science and Cochrane Library, up to December 2023. The control group included placebo or csDMARD. Outcome indicators included American College of Rheumatology 20% response (ACR20), ACR50, ACR70 and the percentage of patients achieving 28-joint disease activity score using C-reactive protein (DAS28(CRP)) ＜ 2.6 at 12 week and 24 week. Data processing, network evidence plots, surface under the cumulative ranking curve (SUCRA) ranking, league plots and funnel plots were generated. Risk ratio (RR) and 95% confidence interval (95%CI) as effect sizes to analyze the statistics.Results: This study included thirty-six RCTs with 16713 patients. All JAK inhibitors were more effective than placebo in ACR20 (RRs ranging between 1.74 and 3.08), ACR50 (RRs ranging between 2.02 and 7.47), ACR70(RRs ranging between 2.68 and 18.13), DAS28(CRP)＜2.6 (RRs ranging between 2.70 and 7.09) at 12 week. Upadacitinib 30mg and upadacitinib 15mg showed relatively good efficacy according to their relative SUCRA ranking. All JAK inhibitors were more effective than csDMARD or placebo in ACR20 (RRs ranging between 1.16 and 1.86), ACR50 (RRs ranging between 1.69 and 2.84), ACR70(RRs ranging between 1.50 and 4.47) , DAS28(CRP)＜2.6 (RRs ranging between 2.28 and 7.56) at 24 week. Upadacitinib 15mg+csDMARD and baricitinib 4mg+csDMARD showed relatively good efficacy according to their relative SUCRA ranking. The safety analysis results such as serious infection, malignancy, major adverse cardiovascular event(MACE), and venous thromboembolic events(VTE) showed no statistical difference.Conclusions: This NMA study indicated that all JAK inhibitors performed better than placebo.